Social impact of end-stage renal disease requiring hemodialysis among patients with type-2 diabetes and their caregivers in Bengaluru, Karnataka - Ishani Hanspal; Farah Naaz Fathima; Prashant G Kedlaya (Wolters Kluwer Medknow Publications, 2021)
Introduction: Diabetic nephropathy is the leading cause of end-stage renal disease (ESRD) requiring hemodialysis. The social impact of a chronic disease like this is far reaching and often difficult to quantify. Objectives: To assess the social impact of ESRD among type 2 diabetics requiring hemodialysis and their caregivers. Methods: A cross-sectional study was carried out between February 2017 and 18 among patients with type 2 diabetes requiring hemodialysis and their caregivers, attending the dialysis unit at St. John's Medical College Hospital, Bengaluru, India. Social impact was assessed under the domains of stress (physiologic and psychologic), quality of life (QOL), cost of care, self-perceived burden, and caregiver burden. Study tools used were semi-structured interview schedule for sociodemographic data, details regarding diabetes, hemodialysis and cost of care, EuroQol-5D-3L, hemodialysis stressor scale, Cousineau Self-Perceived Burden Scale, and Caregiver Burden Scale. Results: A total of 160 participants were included. Majority were males (78%) between 46 and 60 years of age. Most participants experienced moderate stress due to hemodialysis (65%) and moderate self-perceived burden (47.5%). Five (10.6%) participants reported full health, while one (0.6%) reported poor health. Anxiety/depression (80.6%) was the top reported problem among all domains of QOL. Caregiver burden was moderate (53.9%). Annual median cost of direct medical expenditure was ₹258,600 (interquartile range [IQR]: 197,400-433,500) and ₹16,500 (IQR: 9,600-32,100) for nonmedical. Conclusion: We conclude that the social impact of ESRD among type 2 diabetics requiring hemodialysis and their caregivers was moderate. Routine counseling of patients receiving haemodialysis and support groups for patients as well as caregivers will help reduce the impact.